Triterpenes from Ardisia cf. elliptica (subgenus Tinus) limit vascular density and promote von Willebrand factor expression on duck chorioallantoic membrane - Raga, Dennis D. (Animo Repository, 2013)
Mixtures of bauerenol (1a), α-amyrin (1b) and β-amyrin (1c) extracted from the leaves of Ardisia cf. elliptica (subgenus Tinus) were tested at ratios of 2: 2: 1, 2: 2: 3 and 1: 1: 1, respectively, for their angio-suppressive effects on duck chorioallantoic membrane (CAM). Amixture with the maximum proportion of bauerenol (2: 2: 3) was found to be the most effective in limiting the number of blood vessels appearing in a given chorioallantoic membrane segment in a non-concentration-dependent interaction. All the three ratios of components were found effective in promoting intense expression of the von Willebrand factor (F8), but limited expression of epithelial membrane antigen was observed. Results of the present study indicate that the development of vasculature in duck CAM was limited by high expression of F8 along endothelial surfaces, thus suggesting high impact angio-suppressive effects of substances studied. © 2013 Springer Science+Business Media New York.